Secondary Haemophagocytic Lymphohistiocytosis in a Patient with Metaplastic Breast Carcinoma Receiving Anthracycline-Based Chemotherapy: A Case Report - Kogulan Selvanayagam; Sivakumar Jeyalakshmy (Journal of Tropical Health, 2026)
Hemophagocytic lymphohistiocytosis is a rare life-threatening hyperinflammatory syndrome characterized by uncontrolled immune activation and cytokine storm. It may occur secondary to malignancy or immunosuppressive therapies. While often associated with hematological malignancy, hemophagocytic lymphohistiocytosis is exceptionally uncommon in solid tumors like breast carcinoma.We report a case of 69-year-old female with T4bN1M0 metaplastic breast carcinoma (T4bN1M0- Tumor locally spread to skin of the breast, two axillary lymph nodes without distal metastasis) who developed secondary hemophagocytic lymphohistiocytosis following four cycles of doxorubicin-based chemotherapy. She presented with fever, anorexia, giddiness, and confusion. Laboratory workup revealed cytopenias, elevated inflammatory markers, hyperferritinemia, hypofibrinogenemia, and transaminitis. Bone marrow biopsy confirmed the presence of hemophagocytes. Despite broad-spectrum antibiotics, corticosteroids, IV immunoglobulin, and supportive care, the patient’s condition deteriorated, and she succumbed to the illness.This case highlights the diagnostic difficulty of HLH in solid tumor patients receiving neoadjuvant chemotherapy (i.e. Treatment given before surgical intervention to shrink tumor to increase success of surgery) and emphasizes the importance of early suspicion, prompt bone marrow evaluation, timely immunosuppressive therapy, and multidisciplinary collaboration.